2021
DOI: 10.1155/2021/6650327
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Banking System with Shadow Banking on Different Interbank Network Structures

Abstract: With the rapid development of the financial market, the outbreak of systemic risk is affected by many factors, among which shadow banking is considered to be the essential reason to cause financial crisis and destroy the stability of the banking system. In view of the stability of the banking system, considering shadow banking, interbank lending, and complex relationships between banks, a dynamic complex interbank network model with shadow banking under different network structures is proposed. Based on the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In conclusion, the monotonicity and convexity of the probability of credit risk contagion of the carbon quota among firms ψ on carbon performance γ can be proven to be related to the interfirm assessment scores. 10], and γ ∈ (0, 1). At this time, f (−10) < 0 and ∂ 2 ψ ∂F z ij 2 < 0.…”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the monotonicity and convexity of the probability of credit risk contagion of the carbon quota among firms ψ on carbon performance γ can be proven to be related to the interfirm assessment scores. 10], and γ ∈ (0, 1). At this time, f (−10) < 0 and ∂ 2 ψ ∂F z ij 2 < 0.…”
Section: Proofmentioning
confidence: 99%
“…At present, scholars have mainly studied the contagion of counterparty risk from the perspective of traditional finance [5][6][7][8][9][10][11][12]. With the proposed goal of carbon peak and carbon neutrality, green finance has been considered the most important solution [13], and new counterparty risks will be induced in the development of green finance.…”
Section: Introductionmentioning
confidence: 99%
“…The scientists Pan and Fan [20] investigated the current realities regarding stability of the banking system, took into account shadow banking, inter-bank lending and complex relationships between banks, and proposed a dynamic complex model of the inter-bank network with shadow banking under various network structures. As a result of research, it was concluded that the spread of systemic risks between banks is closely related to the structures of the interbank network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shadow banking emerged in the 1960s and 1970s when European and American countries experienced a disintermediation credit crisis, and then the United States carried out a series of financial innovations to break through interest rate controls, such as asset securitization [5], and deregulated the control of the financial sector. This had led to the development of many financial services and financial institutions with the characteristics of shadow banking.…”
Section: The Development and Risks Of Shadow Banking In China 11 The ...mentioning
confidence: 99%